Self-Passivation by Fluorine Plasma Treatment and Low-Temperature Annealing in SiGe Nanowires for Biochemical Sensors. (11th June 2014) - Chang, Kow-Ming; Lai, Chiung-Hui; Chen, Chu-Feng; Kuo, Po-Shen; Chen, Yi-Ming; Chang, Tai-Yuan; Whang, Allen Jong-Woei; Lai, Yi-Lung; Chen, Huai-Yi; Hsieh, Ing-Jar
Abstract : Nanowires are widely used as highly sensitive sensors for electrical detection of biological and chemical species. Modifying the band structure of strained-Si metal-oxide-semiconductor field-effect transistors by applying the in-plane tensile strain reportedly improves electron and hole mobility. The oxidation-induced Ge condensation increases the Ge fraction in a SiGe-on-insulator (SGOI) and substantially increases hole mobility. However, oxidation increases the number of surface states, resulting in hole mobility degradation. In this work, 3-aminopropyltrimethoxysilane (APTMS) was used as a biochemical reagent. The hydroxyl molecule on the oxide surface was replaced by the methoxy groups of the APTMS molecule. We proposed a surface plasma treatment to improve the electrical properties of SiGe nanowires. Fluorine plasma treatment can result in enhanced rates of thermal oxidation and speed up the formation of a self-passivation oxide layer. Like a capping oxide layer, the self-passivation oxide layer reduces the rate of follow-up oxidation. Preoxidation treatment also improved the sensitivity of SiGe nanowires because the Si-F binding was held at a more stable interface state compared to bare nanowire on the SiGe surface. Additionally, the sensitivity can be further improved by either the N2 plasma posttreatment or the low-temperature postannealing due to the suppression of outdiffusion of Ge and F atoms from the SiGe nanowire surface.